Leptin-Induced Sympathetic Nerve Activation: Signaling Mechanisms and Cardiovascular Consequences in Obesity - Rahmouni, Kamal (Current Hypertension Reviews, 2010)
Obesity increases cardiovascular morbidity and mortality in part by inducing hypertension. One factor linking excess fat mass to cardiovascular diseases may be the sympathetic cardiovascular actions of leptin. Initial studies of leptin showed it regulates appetite and enhances energy expenditure by activating sympathetic nerve activity (SNA) to thermogenic brown adipose tissue. Further study, however, demonstrated leptin also causes sympathetic excitation to the kidney that, in turn, increases arterial pressure. In animal studies, elevating circulating leptin levels increased arterial pressure. Moreover, mice with diet-induced obesity have a preserved arterial pressure response to leptin despite the resistance to the metabolic action of leptin and these mice have elevated baseline arterial pressure. Conversely, severely obese, but leptin-deficient, mice and humans display low sympathetic tone and decreased blood pressure. Together, these findings demonstrate that leptin plays a physiological role in maintaining sympathetic tone and blood pressure, and further suggest that hyperleptinemia may contribute to the elevated blood pressure associated with obesity. Consistent with this selectivity in leptin resistance, mounting evidence suggests that the sympathetic nervous system subserving different tissues is differentially controlled by leptin. For instance, different molecular signaling mechanisms are engaged by the leptin receptor to control the regional sympathetic nerve activity. Understanding the mechanisms by which leptin controls the sympathetic nervous system will provide insight into the cardiovascular complications of obesity.
Keywords: Leptin